Β-Blocker Adherence in Familial Long QT Syndrome. (August 2016) - Waddell-Smith, Kathryn E.; Li, Jian; Smith, Warren; Crawford, Jackie; Skinner, Jonathan R.
Abstract : Background—: Long-term uninterrupted β-blockade significantly reduces cardiac events in long QT syndrome (LQTS). Despite this, data on nonadherence are scarce and quantified only on the day of cardiac arrest in LQTS literature. We aimed to describe β-blocker adherence, and predictors thereof, among patients with LQTS types 1 and 2. Methods and Results—: Electronic health records and pharmacy dispensing data were reviewed for 90 patients with LQTS 1 and 2 who reside in Auckland, New Zealand, during a 34-month period. For each patient, the medication possession ratio (MPR: proportion of follow-up days patients were dispensed β-blocker) was calculated. Adequate adherence was characterized by an MPR ≥0.8 and ideal as MPR=1.0. Clinical and demographic features were assessed to determine whether they predicted adherence. Long-term β-blockers were prescribed to 74 patients (82%). Side effects were described as intolerable by 6 (8%) and their β-blockers were stopped. MPR was calculated in the remaining 68 patients >151.7 patient-years of follow-up. Median MPR was 0.79 (range, 0–1.3). Suboptimal adherence (MPR<0.8) was recorded in 35 (51%). Seven patients (10%) never took up a prescription (MPR=0). Adequate adherence was present in 33 (49%), including 9 (13%) who had ideal adherence. Age, sex, clinical presentation, family history of sudden death, ethnicity, and deprivation index did not predict adherence. Conclusions—: Adherence to β-blockers in LQTS is suboptimal in half of those with LQTS 1 and 2. Risk factors for nonadherence could not be identified in our population. Further research into β-blocker adherence is imperative in this high-risk population.